The combined effect of fish oil containing Omega‐3 fatty acids and Lactobacillus plantarum on colorectal cancer. Issue 12 (28th September 2022) - Sharifi, Elahe; Yazdani, Zahra; Najafi, Mojtaba; Hosseini‐khah, Zahra; Jafarpour, Ali; Rafiei, Alireza
Abstract: Colorectal cancer (CRC) is one of the deadliest malignancies. Recent attempts have indicated the role of diet in the etiology of CRC. Natural dietary compounds such as probiotics and Omega‐3 fatty acids that act synergistically can be beneficial in finding a tremendous solution against CRC. To date, the combined effect of fish oil containing Omega‐3 fatty acids (Omega‐3) and Lactobacillus plantarum ( L. plantarum ) on CRC has been left behind. We here evaluated the effects of co‐encapsulation of Omega‐3 and probiotic bacteria on CRC cell lines compared to normal cells. Omega‐3 and L. plantarum bacteria were co‐encapsulated in three ways, including gelatin–gum Arabic, gelatin–chitosan, and chitosan–gum Arabic complex coacervate microcapsules. After treatment of cells (Normal [L929] and colorectal [C26]) by L. plantarum, Omega‐3, and microcapsules, viability and growth capacity of cell lines were measured using the MTT (3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5‐diphenyltetrazolium bromide) assay. Isolated total RNA was used to evaluate the expression profile of BCL2‐associated X protein (BAX), B‐cell lymphoma 2 (BCL‐2), and Caspase‐3 (CASP3) genes by real‐time polymerase chain reaction (PCR). Statistical analysis was performed with SPSS 25 software. A value of p  < .05 was considered statistically significant. The results indicated a significant reduction in cell viability of C26 in a concentration‐dependent manner in the treated cells with all treatments, except gelatin–gum Arabic microcapsules. The messenger RNA (mRNA) expression level of the BAX and CASP3 genes in C26 cells being treated with all treatments significantly increased than in untreated cells, and the expression level of the anti‐apoptotic factor of the BCL‐2 gene decreased in C26 cells simultaneously ( p  < .05). Although, the combined effect of Omega‐3 and L. plantarum and microcapsulated treatments had no more effect on viability and apoptosis gene expression of cancer cells compared to Omega‐3 or L. plantarum . In conclusion, combination therapy with fish oil containing Omega‐3 and L. plantarum does not improve the anticancer effect of each alone. Abstract : The present study showed that Omega‐3 selectively induces cytotoxicity and apoptosis in tumor cells. In addition, the suspension of L. Plantarum and bacteria extract induced apoptosis in cancer cells more than normal cells. The combined effect of L. Plantarum and Omega‐3 did not improve cytotoxicity and apoptosis in colorectal C26 cancer cells compared with monotherapy with L. Plantarum or Omega‐3.